2018
DOI: 10.4049/jimmunol.1800333
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Macrophage FcγR Signaling and Reactive Oxygen Species in Alloantibody-Mediated Hepatocyte Rejection

Abstract: Humoral alloimmunity negatively impacts both short- and long-term cell and solid organ transplant survival. We previously reported that alloantibody-mediated rejection (AMR) of transplanted hepatocytes is critically dependent on host macrophages. However, the effector mechanism(s) of macrophage-mediated injury to allogeneic liver parenchymal cells is not known. We hypothesized that macrophage-mediated destruction of allogeneic hepatocytes occurs by cell-cell interactions requiring Fcγ receptors (FcγRs). To exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…In fact, IL-17-producing Th17 cells are reported to exacerbate tumorigenesis and liver damage (Chang, 2019), while IL-22-producing Th17 cells could facilitate recovery of the liver from injury (Arshad et al, 2020). In regard to macrophages, M1 macrophages, while displaying anti-tumor function, could also cause liver damage (Zimmerer et al, 2018). Very recent analysis revealed that M1 macrophages with an M1 > M2 pattern were associated with aggressive cancer biology without any survival benefit (Oshi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, IL-17-producing Th17 cells are reported to exacerbate tumorigenesis and liver damage (Chang, 2019), while IL-22-producing Th17 cells could facilitate recovery of the liver from injury (Arshad et al, 2020). In regard to macrophages, M1 macrophages, while displaying anti-tumor function, could also cause liver damage (Zimmerer et al, 2018). Very recent analysis revealed that M1 macrophages with an M1 > M2 pattern were associated with aggressive cancer biology without any survival benefit (Oshi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These are phagocytosis, antigen presentation, cytokine production and killing of infected host cells via ADCC. In transplantation, in vitro and in vivo experiments have shown that alloantibody-dependent allograft rejection is mediated by host macrophages through FcγRs and reactive oxygen species (ROS)-related cytotoxic effector mechanisms ( 165 ). In biopsies of kidney allografts, CD68 and CD163 are two main markers used to follow the presence of tissue-resident macrophages and monocyte-derived macrophages ( 151 , 152 , 166 ).…”
Section: Antibody-independent MVImentioning
confidence: 99%
“…Further, ROS is an important contributor to marked up-regulation of the inhibitory costimulatory molecule, PD-L1, leading to immune escape ( 25 ); interestingly, the antioxidants, N-acetyl cysteine (NAC) and apigenin, can offset this change ( 26 ). In addition, alloantibody-FcγR I/FcγR III-dependent ROS production in macrophages is an important mediator of humoral immune damage during liver graft rejection ( 27 ). Opsonization of IgG on IFN-γ-activated macrophages led to diminished phagosomal processing of proteins in a PKC/Syk- NOX2-dependent manner, which occurs at the level of the individual phagosome ( 28 ).…”
Section: Ros and Immune Cellsmentioning
confidence: 99%